NEW RESULTS ON ANCIENT SETTLEMENT PATTERNS IN THE SOUTH-EASTERN QADISIYAH REGION (IRAQ). THE 2016-2017 IRAQI-ITALIAN QADIS SURVEY PROJECT - Abbas, Ahmed (Al-Adab Journal, 2018)
The QADIS survey project is a joint initiative of the Alma Mater Studiorum - University of Bologna and the State Board of Antiquities and Heritage (SBAH). The findings presented here were analyzed in the frame of the EU funded project "EDUU - Educational and Cultural Heritage Enhancement for Social Cohesion in Iraq" (EuropeAid CSO-LA/2016/382-631). The first, second and third field seasons took place in January and October 2016 and in January 2017 respectively. We report here on the general survey activities of the first two seasons, providing detailed information on 40 sites newly identified in addition to Adams 1981. The survey area (Fig. 1) follows the administrative borders of the region of Qadisiyah to the South and East (including part of the Delmej basin), and it stops around the town of Afak to the North-West.1